If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = 2(x + -3) Reorder the terms: 2y = 2(-3 + x) 2y = (-3 * 2 + x * 2) 2y = (-6 + 2x) Solving 2y = -6 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = -3 + x Simplifying y = -3 + x
| -3x-25=23-6x | | 6x-3=29-2x | | 103-26= | | 3x-6=7x+8 | | 6(x-1)=102 | | 6=2x+8 | | 2x=6x-18 | | 2.3x=16.1 | | -9+8x=x-30 | | 4g+4=3g+10 | | c^4-121= | | 4m-1+1= | | 3+-9=X | | 2-x=-4x+2 | | 7-n=5+3n | | 29x^2+5x-24=0 | | 2x-5y+8+3x-y-15= | | -9+X= | | 3x+2=8x-13 | | 4(c-7)=-16 | | 7x=5x-3 | | 5g+2(-4+5g)=1-g | | 24=2x+8 | | 4-2x+8x=20 | | -11(x+12)=3(x+2) | | 200m-100m+47750=51000-150m | | 200-100+47750=51000-150 | | A=bx+p | | 8x-20-2x=20 | | 3t-4=17 | | -8+x+6=0 | | .5y=-.75y-40 |